The RNA-editing enzyme ADAR1: a regulatory hub that tunes multiple dsRNA-sensing pathways. (5th December 2022) - Nakahama, Taisuke; Kawahara, Yukio
Abstract: Adenosine deaminase acting on RNA 1 (ADAR1) is an RNA-editing enzyme that catalyzes adenosine-to-inosine conversions in double-stranded RNAs (dsRNAs). In mammals, ADAR1 is composed of two isoforms: a nuclear short p110 isoform and a cytoplasmic long p150 isoform. Whereas both isoforms contain right-handed dsRNA-binding and deaminase domains, ADAR1 p150 harbors a Zα domain that binds to left-handed dsRNAs, termed Z-RNAs. Myeloma differentiation-associated gene 5 (MDA5) sensing of endogenous dsRNAs as non-self leads to the induction of type I interferon (IFN)-stimulated genes, but recent studies revealed that ADAR1 p150-mediated RNA editing, but not ADAR1 p110, prevents this MDA5-mediated sensing. ADAR1 p150-specific RNA-editing sites are present and at least a Zα domain–Z-RNA interaction is required for this specificity. Mutations in the ADAR1 gene cause Aicardi–Goutières syndrome (AGS), an infant encephalopathy with type I IFN overproduction. Insertion of a point mutation in the Zα domain of the Adar1 gene induces AGS-like encephalopathy in mice, which is rescued by concurrent deletion of MDA5. This finding indicates that impaired ADAR1 p150-mediated RNA-editing is a mechanism underlying AGS caused by an ADAR1 mutation. ADAR1 p150 also prevents ZBP1 sensing of endogenous Z-RNA, which leads to programmed cell death, via the Zα domain and its RNA-editing activity. Furthermore, ADAR1 prevents protein kinase R (PKR) sensing of endogenous right-handed dsRNAs, which leads to translational shutdown and growth arrest. Thus, ADAR1 acts as a regulatory hub that blocks sensing of endogenous dsRNAs as non-self by multiple sensor proteins, both in RNA editing-dependent and -independent manners, and is a potential therapeutic target for diseases, especially cancer. Abstract : How ADAR1 regulates immune responses triggered by dsRNA Graphical Abstract: